Unmet need for contraception among urban women: a cross sectional study in Puducherry - V., Sudha; H. N., Vrushabhendra; S., Srikanth; E., Suganya (International Journal Of Community Medicine And Public Health, 2017)
Background: Providing universal family planning services is an important strategy to reduce maternal morbidity and to control population growth. Worldwide, when contraception is used properly and effectively to avoid unwanted pregnancy it can reduce 25–35% of maternal deaths. The present study aimed at measuring the proportion of married women with unmet need for family planning in an urban area of Puducherry. Methods: A cross sectional study was conducted among 235 married women in the urban field practice area of Sri Venkateshwara Medical College Hospital & Research Centre, Puducherry. Participants were selected based on predetermined eligibility criteria using systematic random sampling method. SPSS version 23.0 was used for statistical analysis. Proportion, Mean, Standard deviation and Logistic regression were applied to interpret the results. Results: Mean age of the participants was 33.3 ±6 years, Nearly 77 %( 181) of the participants reported having used any method of contraceptive at least once and 34.5 %( 81) were found to have unmet need for family planning. The most common reason for unmet need for contraception was fear of side effects (39.5%) and others were infrequent sex (12.3%),insisted by family members (12.3%) and religious reasons (12.3%). Conclusions: Unmet need for family planning was found to be fairly high in our study population. Health care personnel, preferably field staff should be trained to give an informed choice of contraception to the eligible couples to reduce the unmet need for contraception.